THE IMPACT OF KAMPUS MENGAJAR PROGRAM ON STUDENTS"™ CAREER PLANNING - Hasanah, Nadiyatul; Muamaroh, Muamaroh (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
Existing research so far has focused more on the influence of Kampus Mengajar program on teaching skills and academic achievement, leaving a significant knowledge gap in understanding its role in career planning. So, the aim of the research to find out the motivation of students to participate in the Kampus Mengajar program and whether the Kampus Mengajar program has an impact on students"™ career planning. The subjects consisted of 42 seventh-semester English Education students at Universitas Muhammadiyah Surakarta, Indonesia. Utilizing a sequential explanatory design, the research instrument used questionnaires and interviews. Data analysis was carried out using quantitative and qualitative analysis. The findings revealed three primary motivations in participating the program: gaining educational experience, developing professional competencies, and building inter-university relationships. Statistical analysis using Pearson correlation revealed a significant positive correlation (r = 0.390, p = 0.011) between Kampus Mengajar participation and career planning, indicating that the program positively impacts on students' career planning. The study concludes that the Kampus Mengajar program serves as a valuable experiential learning platform, providing students with practical insights, professional skill development, and career interest exploration beyond academic settings.